“There’s room to do more”: a mixed-methods study of the Temporary Assistance for Needy Families (TANF) diversion program and intimate partner violence in Georgia - Jahangir, Tasfia; Dahn, Conjay; Devakottai, Ria; Livingston, Melvin D.; Woods-Jaeger, Briana (Frontiers in Public Health, 2024)
Introduction Intimate partner violence (IPV) is a risk factor for homicides and suicides. As poverty is both a predictor and a consequence of IPV, interventions that alleviate poverty-related stressors could mitigate IPV-related harms. Temporary Assistance for Needy Families (TANF), a monthly cash assistance program, is one such potential intervention. In the state of Georgia, the TANF diversion program, which provides a non-recurrent lump-sum payment to deter individuals from monthly TANF benefits, is an understudied component of TANF that may influence the effectiveness of state TANF programs in supporting IPV survivors. Aim This study quantifies and qualifies the role of Georgia’s TANF diversion program in shaping IPV-related mortality. Methods This study relies on a mixed-methods sequential explanatory design. Using data from the Georgia Violent Death Reporting System (GA-VDRS), an interrupted time series analysis was conducted to estimate the effect of TANF diversion on IPV-related homicides and suicides. Semi-structured interviews were then administered with TANF policy experts and advocates, welfare caseworkers, and benefit recipients (n = 20) to contextualize the quantitative findings. Results The interrupted time series analysis revealed three fewer IPV-related deaths per month after implementing TANF diversion, compared to pre-diversion forecasts (coefficient = −3.003, 95%CI [−5.474, −0.532]). However, the qualitative interviews illustrated three themes regarding TANF diversion: (1) it is a “band-aid” solution to the access barriers associated with TANF, (2) it provides short-term relief to recipients making hard choices, and (3) its limitations reveal avenues for policy change. Discussion While diversion has the potential to reduce deaths from IPV, it may be an insufficient means of mitigating the poverty-related contributors to IPV harms. Its limitations unveil the need for improved programs to better support IPV survivors.